Conformational Preferences, Experimental And Theoretical Vibrational Spectra Of Cyclo(Gly-Val) Dipeptide - Çelik, Sefa; Özel, Ayşen; Kecel, Serda; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2011)
The theoretical conformational analysis of cyclic dipeptide, cyclo(glycine-valine), which has anticancer activity, has been performed by molecular mechanics method, in order to examine the energetically optimal conformational states. The relative positions of the side chain residues of the stable conformations of dipeptide were obtained. The obtained geometry of the most stable conformation of the cyclo(Gly-Val) was optimized using DFT method at B3LYP/6-31++G(d,p) level of theory. Afterwards dimeric forms of the dipeptide were formed and energetically preferred conformations of dimers were investigated using the same method and the same level of theory. The experimental IR and micro-Raman spectra of solid cyclo(Gly-Val) were reported for the first time. The vibrational normal modes and associated wavenumbers. IR intensities and Raman activities of the monomeric and dimeric forms of the dipeptide were calculated using OFT method at B3LYP/6-31++G(d,p) level of theory and the results were compared with the experimental data. The total energy distributions (TED) of the vibrational modes were calculated by using Scaled Quantum Mechanical (SQM) analysis. Vibrational assignment was performed on the basis of calculated total energy distribution (TED) of the modes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: conformational analysis; cyclic dipeptide; density functional theory; IR and raman spectra; glycine; valine; crystal-structure; raman; diketopiperazine; spectroscopy; molecule; konformasyon analizi; halkalı dipeptid; yoğunluk fonksiyonu teorisi; IR ve Raman spektrumları; glisin; valin; kristal yapı; diketopiperazin; spektroskopisi; molekül